Small-Scale Habitat Conditions Are More Important Than Site Context for Influencing Pollinator Visitation - Berthon, Katherine; Meyer, Sebastian T.; Thomas, Freya; Frank, Andrea; Weisser, Wolfgang W.; Bekessy, Sarah (Frontiers in Ecology and Evolution, 2021)
The ability of insects to persist in urban greenspace depends on their ability to usefully interact with available plant resources. Greenspace design influences plant-insect interactions by: 1) limiting the plant-species pool available for interaction through plant choice, 2) limiting the insects that are available for interaction through site-occupancy dynamics; and 3) mediating insect preferences based on the context of particular plant-insect interactions through structural barriers, microclimatic changes or competition. We designed an experiment to measure the effect of greenspace design attributes on site occupancy and insect preferences while keeping plant availability constant. Using a set of 5 functionally distinct flowering plant species (‘phytometres’), we used occupancy-detection modelling to test factors affecting probability of visitation for eight groups of pollinating insects (ants, beetles, butterflies, bumblebees, honeybees, small bees, hoverflies and other flies) across 102 urban squares in Munich, Germany. We found that the probability of detecting an interaction was low for most functional groups, and situational factors, such as weather or competition from co-occurring flowers, were the primary drivers of visitation. Increasing the proportion of unsealed surfaces and quantity or diversity of flowers on the site had a positive influence on the probability of interaction, and, to a lesser extent, on probability of occupancy. Landscape connectivity and site area were important for only a few groups. Together, our results suggest that small-scale habitat conditions are more important than site context for influencing pollinator visitation. Designers can encourage interaction through contiguous provision of floral resources and unsealed surfaces while limiting internal barriers.